Learning how to break bad news from worked examples: Does the presentation format matter when hints are embedded? Results from randomised and blinded field trials. Issue 9 (September 2020) - Schmitz, Felix Michael; Schnabel, Kai Philipp; Bauer, Daniel; Woermann, Ulrich; Guttormsen, Sissel
Highlights: The success of learning how to break bad news from a worked example (WE) can vary. Studying the WE as video or text equally impacts student breaking-bad-news skills. Skills significantly increase when the WE (whether as text or video) involves hints. Independent of their presentation, WEs with hints can lead to increased learning. Abstract: Objectives: Video-based worked examples enable medical students to successfully prepare for breaking-bad-news (BBN) encounters with simulated patients (SPs). This is especially true when examples include hints that signal important content. This paper investigates whether the beneficial effect of hints only applies to video-based worked examples or also text-based examples. Methods: One-hundred-and-forty-seven fourth-year medical students attending a BBN training participated in either of two equally scaffolded, randomised field trials. Prior to encountering SPs, the students worked through an e-learning module introducing the SPIKES protocol for delivering bad news; it contained the same worked example presented to either of four groups as text or video, with or without additional hints denoting the SPIKES steps being implemented. Results: Only a main effect of 'hints' was revealed, implying that students in the hints groups delivered the news to an SP significantly more appropriately than those in the without-hints groups. Conclusions: Independent of their presentation format, worked examples with hints best foster students' BBN skills learning. Practice implications: In addition to video, text-based worked examples can effectively prepare students for BBN simulations if hints are included. This offers an affordable alternative to video examples, as text examples can be generated with less effort.